Pancasila sebagai Landasan Komunikasi yang Berkeadilan an Berkelanjutan - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya; Zaki Ramdhani Wicaksono; Muhammad Asziv Amalia; Ruditri Setyawan; Aprilia Ningpitasari (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Pancasila is foundational ideology of Indonesia, serving as a guiding principle across various aspects of life, including fair and sustainable communication. Klean (2013) states that